Uterine lipoleiomyoma: rare presentation of postmenopausal bleeding - Sahay, Nehal; Sahay, Vinita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine lipoleiomyomas are rare benign tumors composed of mature adipose tissue and smooth muscle cells. They account for less than 0.2% of all uterine neoplasms and are typically asymptomatic, often discovered incidentally. Symptomatic cases presenting with postmenopausal bleeding are exceedingly rare. A 63-year-old postmenopausal woman presented with intermittent vaginal bleeding for one month. Imaging revealed a well-defined hyperechoic mass in the posterior uterine wall. Magnetic resonance imaging (MRI) confirmed the fat-containing lesion suggestive of lipoleiomyoma. She underwent total abdominal hysterectomy. Histopathology confirmed uterine lipoleiomyoma with no evidence of malignancy. Although rare, uterine lipoleiomyoma should be considered in the differential diagnosis of postmenopausal bleeding. Radiological evaluation is key, but histopathological confirmation is essential.